Search for anomalous Wtb couplings and flavour-changing neutral currents in t-channel single top quark production in pp collisions at ?s=7 and 8 TeV - The, C. M. S. collaboration; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Erö, J.; Flechl, M.; et al. (My University, 2017)
Single top quark events produced in the t channel are used to set limits on anomalous Wtb couplings and to search for top quark flavour-changing neutral current (FCNC) interactions. The data taken with the CMS detector at the LHC in proton-proton collisions at s=7 and 8 TeV correspond to integrated luminosities of 5.0 and 19.7 fb?1, respectively. The analysis is performed using events with one muon and two or three jets. A Bayesian neural network technique is used to discriminate between the signal and backgrounds, which are observed to be consistent with the standard model prediction. The 95% confidence level (CL) exclusion limits on anomalous right-handed vector, and left- and right-handed tensor Wtb couplings are measured to be |fV R| < 0.16,?|fT L| < 0.057, and ? 0.049 < fT R < 0.048, respectively. For the FCNC couplings ?tug and ?tcg, the 95% CL upper limits on coupling strengths are |?tug|/? < 4.1 × 10? 3 TeV?1 and |?tcg|/? < 1.8 × 10? 2 TeV?1, where ? is the scale for new physics, and correspond to upper limits on the branching fractions of 2.0 × 10?5 and 4.1 × 10?4 for the decays t ? ug and t ? cg, respectively.[Figure not available: see fulltext.] © 2017, The Author(s).
Citation: The, C. M. S. c., Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., . . . Woods, N. (2017). Search for anomalous Wtb couplings and flavour-changing neutral currents in t-channel single top quark production in pp collisions at ?s=7 and 8 TeV. Journal of High Energy Physics, 2017(2). doi:10.1007/JHEP02(2017)028
Keywords: Flavour Changing Neutral Currents; Hadron-Hadron Scattering (Experiments); Top Physics